(untitled) - Cloud, Nancy (Boston, Mass., 2000)
Dual Language Instruction: A Handbook for Enriched Education is an ideal professional reference title for those interested in teaching ESL, foreign language, and bilingual programs. It ts a resource guide for implementing, evaluating, administering, and maintaining dual language instruction programs.
Keywords: English language,Education, Bilingual,Ngôn ngữ Anh,Giáo dục, Song ngữ; Study and teaching,Dạy và học; United States,United States,Nước Mỹ,Nước Mỹ